INCLUSION TECH: Integrasi Sistem Screening ABK, Pendampingan Orang Tua, dan Pelatihan Manajemen untuk Optimalisasi Layanan Disabilitas di Denpasar - Ni Wayan Cahya Ayu Pratami; Wayan Widya Artana; Komang Yogi Triana (Pusat Riset dan Inovasi Nasional, 2025)
The Inclusion Tech community service program was carried out in collaboration with the Disability Service Center (UPTD PLD) of Denpasar City. The program focused on three main issues: the absence of standardized service Standard Operating Procedures (SOPs), the lack of an integrated screening system for children with special needs, and limited parental understanding of basic stress management knowledge. The solutions offered included training on SOP development, the creation of a mobile- and web-based screening application, stress management training for parents, and the provision of therapeutic equipment to support rehabilitation. The results showed that 100% of administrative staff (33 individuals) successfully developed and consistently implemented SOPs. In addition, a digital system was created that enables therapy management as well as early screening. Pre-test and post-test evaluations demonstrated that 80% of parents improved their understanding of stress management. The program also provided three therapeutic devices—a standing table for children with cerebral palsy, a pediatric walker, and a Plum Junior trampoline—that proved effective in strengthening therapy services and expanding the range of rehabilitative interventions. Overall, the findings highlight that the integration of managerial capacity building, technological innovation, and psychosocial support can significantly improve the quality of disability services at the local level while contributing to the achievement of SDGs 3 (Good Health and Well-being), 4 (Quality Education), and 10 (Reduced Inequalities).